Obstetric Brachial Plexus Palsy and Functional Implications: Which Joint in the Upper Extremity Is More Closely Associated? - Gülsena Utku Umut; Zeynep Hoşbay; Müberra Tanrıverdi; Güleser Güney Yılmaz; Okyar Altaş; Alperen Korucu; Atakan Aydın (Medicina)
Background and Objectives: The objective of this study is to examine the correlation between the active range of motion (ROM) of the affected upper extremity and functional capacity in children with Obstetric Brachial Plexus Palsy (OBPP) who have undergone the modified Hoffer tendon transfer technique. Materials and Methods: The study cohort comprised 52 children with OBPP, aged 4–14 years, who had undergone a shoulder tendon transfer. The ROM was quantified using a goniometer, while functionality was evaluated through the administration of the Brachial Plexus Outcome Measure (BPOM). Results: The study identified significant correlations between the shoulder ROM and the Brachial Plexus Outcome Measure (BPOM). Specifically, shoulder flexion (p = 0.017; r = 0.351) was positively associated with shoulder functionality, while shoulder internal rotation (p = 0.001; r = 0.481) was linked to appearance scores. A significant negative relationship was observed between elbow extension (p < 0.001; r = −0.512) and elbow and forearm activities. Conclusions: The study highlights the necessity of assessing both joint range of motion and body perception for effective treatment and follow-up, to improve the functionality and quality of life for children with OBPP.